Mathematical model for selecting the best technology for restoring road construction machines - Belyaev Aleksandr; Gordienko Valeriy; Druzhinin Petr; Evtukov Sergey (E3S Web of Conferences, 2020)
The article considers the problem of effective and high-quality restoration of road construction machines and equipment. Operational features of reliable and high-precision equipment for road and construction works require high costs for maintaining the operability of machines. Since mainly foreign-made equipment is used, replacing worn-out, especially functionally important parts is very costly. To ensure the requirements of reliable and safe operation of road construction machines, a systematic approach to solving these problems is required, which is decided by the authors through developing an original model of the optimal choice of energy efficient technology for the restoration of parts of road construction machines, with the goal being the highest quality of the part after restoration.